Workers' compensation Law - Jasper, Margaret C. (Oceana, 2008)
Are you an employee who suffered a work-related injury or illness and as a result became disabled and unable to work? You may be entitled to receive certain benefits under a system known as workers' compensation. Although state workers' compensation laws may vary, this publication sets forth a general discussion of the common characteristics of a state workers' compensation system.